Watching the moon and other plays - Bontempelli, Massimo, 1878-1960 (Italica Press Renaissance and modern plays series., 2013)
Patricia Gaborik presents an introduction on the thought and legacy of Massimo Bontempelli (1878-1960), an extremely influential and controversial figure of Italian letters. Includes complete translations of three of his major plays: Watching the Moon (1916) a densely layered response to the era's avant-gardism, with traces of symbolism, expressionism and futurism: the story of a woman who attempts to rescue her (dead) daughter; Stormcloud (1935) pointing fingers at individual behaviors and especially at personal egotism in the face of love and death; and Cinderella (1942), fearless, radical a.